1999
DOI: 10.1046/j.1365-2672.1999.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient subtyping of Yersinia enterocolitica bioserotype 4/O:3 with pulsed-field gel electrophoresis

Abstract: The purpose of this study was to evaluate the efficiency of pulsed‐field gel electrophoresis (PFGE) for differentiation of isolates of Yersinia enterocolitica bioserotype 4/O:3 recovered from pig tongues at retail level in the Helsinki area during October and November of 1996. NotI generated 15 different PFGE patterns for 128 isolates. The discriminatory index did not exceed 74% due to the presence of two predominant PFGE‐types, NA1 (58/128) and NB1 (25/128). After preliminary investigations with 35 enzymes, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 21 publications
(66 reference statements)
1
39
1
1
Order By: Relevance
“…A local reference strain from which amplicons have been sequenced is sufficient for gel-to-gel comparison. Since the results of MLVA are integers, the genotypes determined in different laboratories may be easily compared and joint databases can be produced, as shown in various studies (18,29 (11). Overall, the data showed that on a countrywide scale, MLVA would offer a higher discriminatory power for Y. enterocolitica 4/O3 than the methods mentioned above.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…A local reference strain from which amplicons have been sequenced is sufficient for gel-to-gel comparison. Since the results of MLVA are integers, the genotypes determined in different laboratories may be easily compared and joint databases can be produced, as shown in various studies (18,29 (11). Overall, the data showed that on a countrywide scale, MLVA would offer a higher discriminatory power for Y. enterocolitica 4/O3 than the methods mentioned above.…”
Section: Discussionmentioning
confidence: 86%
“…Biochemical differentiation (biotyping), the most simple and widely available method, is able to separate Y. enterocolitica O3 into biotypes 2, 3, and 4, with biotype 4 (BT4) causing the majority of clinical cases (11,12,20). Most Y. enterocolitica 4/O3 isolates belong to phage type VIII (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The strains belonged to serotypes O:3 (n ϭ 363), O:9 (n ϭ 9), and O:5,27 (n ϭ 7). We previously divided all serotype O:3 strains into 81 genotypes using PFGE with the enzyme NotI, and we divided 206 of those strains into 105 genotypes using the additional enzymes ApaI and XhoI (16,17,(24)(25)(26). The strains were grown on tryptic soy agar (Difco, Lawrence, KS) at 28°C for 18 to 24 h, and the DNA was extracted using guanidium thiocyanate (27).…”
Section: Methodsmentioning
confidence: 99%
“…The epidemiological studies clearly showed a close epidemiological relationship among the analyzed strains. The PFGE method has been extensively used to analyze the epidemiological relationship among strains of Y. enterocolitica (1,6,8,11). In our study the same discriminatory power for both REP-PCR and PFGE was observed.…”
mentioning
confidence: 99%